Presence and genetic diversity of enteric protists in captive and semi-captive non-human primates in côte d'Ivoire, Sierra Leone, and Peru. (April 2022) - Köster, Pamela C.; Lapuente, Juan; Pizarro, Andrea; Prieto-Pérez, Laura; Pérez-Tanoira, Ramón; Dashti, Alejandro; Bailo, Begoña; Muadica, Aly S.; González-Barrio, David; Calero-Bernal, Rafael; Ponce-Gordo, Francisco; Carmena, David
Abstract: Little information is currently available on the occurrence and genetic diversity of pathogenic and commensal protist species in captive and semi-captive non-human primates (NHP) resident in zoological gardens or sanctuaries in low- and medium-income countries. In this molecular-based study, we prospectively collected individual faecal samples from apparently healthy NHP at the Abidjan Zoological Garden (AZG) in Côte d'Ivoire, the Tacugama Sanctuary (TS) in Sierra Leone, and the Quistococha Zoological Garden (QZG) in Peru between November 2018 and February 2020. We evaluated for the presence of pathogenic ( Cryptosporidium spp., Entamoeba histolytica, Giardia duodenalis, Blastocystis sp., Enterocytozoon bieneusi, Balantioides coli ) and commensal ( Entamoeba dispar, Troglodytella abrassarti ) protist species using PCR methods and Sanger sequencing. Giardia duodenalis was the most prevalent species found (25.9%, 30/116), followed by Blastocystis sp. (22.4%, 26/116), and E. dispar (18.1%, 21/116). We detected E. bieneusi (4.2%, 1/24) and T. abrassarti (12.5%, 3/24) only on NHP from AZG. Cryptosporidium spp., E. histolytica, and B. coli were undetected at the three sampling sites investigated here. Sequence analyses revealed the presence of zoonotic sub-assemblages BIII ( n  = 1) in AZG and BIV ( n  = 1) in TS within G. duodenalis . We identified Blastocystis subtype ST3 (100%, 6/6) in AZG, ST1 (80.0%, 12/15), ST2 (6.7%, 1/15), and ST3 (13.3%, 2/15) in TS, and ST2 (80.0%, 4/5) and ST3 (20.0%, 1/5) in QZG. The only E. bieneusi isolate detected here was identified as zoonotic genotype CAF4. Our PCR-based data indicate that potentially pathogenic protist species including G. duodenalis, Blastocystis sp., E. bieneusi, and B. coli are present at variable rates in the three NHP populations investigated here. The identification of zoonotic genotypes within these species indicates that human-NHP transmission is possible, although the extent and directionality of these events need to be elucidated in future molecular surveys. Graphical abstract: Image 1 Highlights: Giardia and Blastocystis are highly prevalent in confined non-human primates. Diarrhoea-causing Cryptosporidium and Entamoeba histolytica were undetected. First description of Enterocytozoon bieneusi genotype CAF4 in non-human primates. Confined non-human primates harbour protist species with zoonotic potential. Cross-species (including human) transmission is possible in zoos and sanctuaries.